Angelo Agostini and the War Against Paraguay: A Brief Biographical Analysis (Ágora Journal, 2024)
Angelo Agostini is one of the leading figures in Brazilian press in the 19th century. The Piedmontese, who settled in Brazil, worked for a series of periodicals, expressing his opinions on various subjects through his sharp lithographs. Regarding the war against Paraguay, Agostini was an active critic of the measures taken by the Empire, while also supporting the efforts of Brazilian soldiers. Therefore, this article aims to present his perceptions of the conflict, as well as the changes in his stance during the war, something observed through his visual productions from 1864 to 1870.
Keywords: Angelo Agostini; press; war against Paraguay.